2022
DOI: 10.1186/s12903-022-02690-5
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm elimination from infected root canals using four different single files

Abstract: Introduction Enterococcus faecalis (E. faecalis) is the most commonly isolated bacterium from infected root canals. It is found in the form of a biofilm, which makes it more resistant to antimicrobials, and requires optimal chemomechanical strategies to maximize root canal disinfection. Aim To evaluate the efficacy of 4 different endodontic file systems against E. faecalis biofilm growth in root canals using colony-forming units per milliliter (CFU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The authors reported that none of these commercial solutions could disrupt or eliminate the biofilm compared with NaOCl, which showed a 100% depletion of bacteria in the biofilm. In another study, the E. faecalis biofilm was not completely removed despite using NaOCl and four different techniques to prepare the root canal [ 41 ]. In our study, a bacterial depletion > 90% was observed for the combined treatment (Cel-AmC).…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that none of these commercial solutions could disrupt or eliminate the biofilm compared with NaOCl, which showed a 100% depletion of bacteria in the biofilm. In another study, the E. faecalis biofilm was not completely removed despite using NaOCl and four different techniques to prepare the root canal [ 41 ]. In our study, a bacterial depletion > 90% was observed for the combined treatment (Cel-AmC).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the simulation of body temperature was deemed critical, as temperature changes were predicted to affect the XP-endo Shaper expansion properties. For standardization, all rotary instruments were used for reaching the full working length in an in-and-out pecking motion with light brushing motion was applied regarding the buccal and lingual walls to improve the file contact with the canal surfaces [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…This helped the evaluator easily detect canal areas that had been touched by the rotary instrument, which ensured reliable calculations while minimizing bias. AutoCAD was used to study different parameters, such as measuring root canal curvature, calculating the number of touched canal walls, determining the instrument's cross-sectional measurements, assessing instrument shaping ability, and during root canal retreatment to evaluate efficacy of various instruments in removing gutta-percha and sealer [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has compared the first launched AF F One single‐file NiTi rotary system (size 25, 0.06 taper; Fanta Dental Material Co.) that is made of a proprietary AF‐R wire technology to various rotary and reciprocating systems. These studies showed that AF F One instruments had lower cyclic fatigue resistance than 2Shape instrument after clinical usage (Ubaed & Bakr, 2022), produced more debris but better cleaning ability than One Shape and OneCurve systems (Mogahed et al, 2021), had better shaping ability than a prototype instrument in simulated canals (Di Nardo et al, 2020), were less effective than certain reciprocating systems in removing calcium silicate‐based sealer (Madarati et al, 2023) and in eliminating Enterococcus faecalis biofilm from infected root canals (Hamed et al, 2022), but showed improved resistance to flexural fatigue compared with a prototype instrument (Gambarini et al, 2019). These preliminary findings indicate that using flat design instruments instead of other market‐available options may not offer the advantages claimed by manufacturers, and further research is necessary to assess their mechanical performance.…”
Section: Introductionmentioning
confidence: 99%